Rollover of apparent wave attenuation in ice covered seas - Li, Jingkai (2018)
Wave attenuation from two field experiments in the ice‐covered Southern Ocean is examined. Instead of monotonically increasing with shorter waves, the measured apparent attenuation rate peaks at an intermediate wave period. This “rollover” phenomenon has been postulated as the result of wind input and nonlinear energy transfer between wave frequencies. Using WAVEWATCH III®, we first validate the model results with available buoy data, then use the model data to analyze the apparent wave attenuation. With the choice of source parameterizations used in this study, it is shown that rollover of the apparent attenuation exists when wind input and nonlinear transfer are present, independent of the different wave attenuation models used. The period of rollover increases with increasing distance between buoys. Furthermore, the apparent attenuation for shorter waves drops with increasing separation between buoys or increasing wind input. These phenomena are direct consequences of the wind input and nonlinear energy transfer, which offset the damping caused by the intervening ice.